Factors Associated with Dietary Calcium Intake and Bone Mineral Density Among Postmenopausal Women in Tehran, Iran - Tajik, Esra (2011)
Osteoporosis is characterized by a decrease in the strength and density of bone with no clinical symptoms until fractures occur. Osteoporotic fracture is a major cause of morbidity and premature death in elderly. This is a descriptive cross-sectional study that aimed to determine factors associated with dietary calcium intake and bone mineral density among 299 postmenopausal women aged 50-65 years old in National Iranian Oil Company (NIOC) Central Hospital. This hospital is located in center of the city and accesibilty was easy for respondents to attend this research. Measurements included information on demographic and socio-economic factors and reproductive history using quesionnaire, dietary intake using 24-houres dietary recall and semi-Food Frequency Questionnaire (SFFQ), physical activity using International Physical Activity Questionnaire (IPAQ - short form), anthropometry (Body Mass Index (BMI), weight and height) using using Seca digital scale and Seca body meter and bone mineral density (BMD) using Dual Energy X-Ray method (DEXA). The mean age of the women was 56.34 ± 4.46 years old with 65.8% were married. About a quarter of the respondents (26.6%) were in normal range of BMI but the majority were overweight (52.9%) and obese (20.4%). Most of the women (91.6%) were sufficiently active and 6.7% had low activity level. Only 1.7% of them had vigorous activity level. The mean calcium intake was 965.33 ± 396.42 mg with 664.70 ± 2.19 mg from food and 302.31 ± 3.39 mg from dietary supplement. About 73% of the respondents had calcium intake less than the DRI (Dietary Reference Intake) and only one third of subjects (31.9%) consumed dietary calcium supplement. SFFQ showed that the major (66.8%) source of calcium intake was dairy products. The BMD of lumbar spine L2-L4 was 1.08 ± 0.14 g/cm2. About 2/3 of the respondents had normal BMD at spine while others were either osteopenic (32.1%) and osteoporotic (1.3%). The mean BMD (g/cm2) of left and right femoral neck and also total femoral neck (both sides) were 0.96 ± 0.07, 0.97 ± 0.09 and 0.97 ± 0.08, respectively. At femoral neck, 67.9% of the respondents had normal BMD while 30.8% and 1.3% were osteopenic and osteoporotic, respectively. Higher calcium intake was associated with higher intake of vitamin D and phosphorous, older age at menopause and higher years of education. In addition, postmenopausal women with lower protein intake and BMI were found to have higher intake of calcium (R2 = 0.369, p < 0.001). Respondents with higher household income per capita (OR,0.997; CI,0.995-1.002) and higher intake of calcium (OR,0.993; CI,0.990-0.996) were significantly protective against osteopenia/osteoporosis of lumbar spine. Respondents with larger household size had 2.3 times the risk of osteopenia/osteoporosis (OR,2.269; CI,1.345-3.827) compared to subject with smaller household size. In addition, higher intake of calcium (OR,0.994; CI,0.992-0.997) was significantly protective against at risk osteopenia/osteoporosis of femoral neck. As a conclusion, these findings indicated that most of the respondents had calcium intake less than DRI. About one third of the respondents had osteopenia and osteoporosis at lumbar spine and femoral neck. There is a need to develop appropriate educational programs to improve nutritional knowledge and to create awareness about the importance of exercise to get optimal bone health and doing annual densitometry to detect women at risk.